Basic Structure of the Pharmacophore Virtual Screening Protein 7kg7 for Candidate Therapeutic Options COVID-19 - Al Fiqri, Ahmad Ridha (Indonesian Journal of Medical Chemistry and Bioinformatics, 2024)
Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome, namely coronaviruses (SARS-CoV-2) has been a pandemic to date and is contagious with relatively high mortality rates. Various efforts have been made to control the pandemic to finding the best solution to reduce the spread such as rapid detection based on molecular and serological, as well as efforts to find the best medicine for COVID-19 patients continue to be carried out. We analyzed and concluded that the presatovir compound is capable of being a substitute for the native protein ligand 7KG7, this is proved with a ΔG value of -13.22 kcal/mol and a constant inhibition value of 202.12 pM smaller than the native ligand. Other compounds such as tipranavir and montelukast with ΔG values of -10.99 and -10.81 kcal/mol as well as constant inhibition values at 11.95 and 8.77 nM also indicate that the three test ligands are better than the native ligands. Another supporting factor of this finding was the fact that test ligands were discovered to possess hydrogen bonds that were either greater than or equivalent to those of the initial ligand. The third test ligand exhibited a promising affinity as a possible substitute for native ligand, however, it is imperative to carefully evaluate and take into account the ADMETOX (Absorption, Distribution, Metabolism, Excretion, and Toxicology) elements before to proceeding with the in-vitro or in-vivo phase.